Public-Private Partnership in the Framework of Waste Management into Electrical Energy in Jatibarang Landfill, Semarang City - Azaria Eda Pradana; Retno Sunu Astuti; Budi Puspo Priyadi (Journal of Local Government Issues (LOGOS), 2020)
In recent years, especially in big cities, the waste problem has begun to be addressed through a private-public cooperation scheme that is supported by technological upgrades. The purpose of this research is to analyze the public-private cooperation mechanism that involves processing waste into electrical energy at Jatibarang Landfill, Semarang, and to identify the inhibiting factors using the theory of implementation "5 right" by Riant Nugroho. This research used a qualitative approach with a descriptive type. The analysis technique for obtaining data was through observation, interviews, and documentation. The results of this study indicate that through the Public-Private Partnership scheme which is based on the principles of Public-Private Partnership, stakeholders can provide and get benefits at the same time if they can mutually align their visions and implement the scheme according to what has been determined. Also, accuracy in the implementation must be considered to be able to achieve the success of Public -Private Partnership.